2014
DOI: 10.1080/09297049.2014.945408
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition in Williams syndrome and Down syndrome: A matching and developmental study

Abstract: Citation for published item:wrt¡ %nezEgstillD F nd furtD wF nd forgttiD F nd qglirdiD gF @PHISA 9pil emotion reognition in illims syndrome nd hown syndrome X mthing nd developmentl studyF9D ghild neuropsyhologyFD PI @SAF ppF TTVETWPF Further information on publisher's website: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 90 publications
(158 reference statements)
3
17
2
Order By: Relevance
“…It also corroborates the study by Pochon and Declercq [24] of children with DS, which made use of static stimuli (photos). On the other hand, the results differ from those observed in earlier studies that used static stimuli, along with emotional vocabulary [9,10,14,15,25] or with dynamic stimuli and production of emotional vocabulary [27]. The original feature in this study was the design of a so-called “nonverbal” task, in the sense that language comprehension and production, particularly of emotional words, was not mobilized in any way for the recognition of emotions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It also corroborates the study by Pochon and Declercq [24] of children with DS, which made use of static stimuli (photos). On the other hand, the results differ from those observed in earlier studies that used static stimuli, along with emotional vocabulary [9,10,14,15,25] or with dynamic stimuli and production of emotional vocabulary [27]. The original feature in this study was the design of a so-called “nonverbal” task, in the sense that language comprehension and production, particularly of emotional words, was not mobilized in any way for the recognition of emotions.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the administration of tasks that make use of dynamic stimuli—which are more ecological—appears to be more appropriate for assessing participants with DS than traditional tasks with static stimuli; that is true of this study and the one by Channell et al [23], which did not find evidence at that time of the deficits mentioned [9,10,17,18,25]. Nevertheless, Martínez-Castilla et al [27], despite their use of animated faces (morphing), found that participants with DS had more problems than TD participants and those with WS, but as they point out, the task was a labeling task, which requires productive verbal skills. Thus, the participants with DS could have been at a disadvantage.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Initial evidence has suggested that accuracy is higher for the emotion happy than for negative emotions, such as anger or fear (Plesa-Skwerer et al 2006;Porter et al 2007), although this may not be the case when methodological problems are overcome (Martínez-Castilla et al 2015). Nevertheless, autonomic arousal levels in response to negative emotions, such as sad or angry, have been found to be lower in individuals with WS than in comparison groups matched for age or for IQ, suggesting decreased vigilance (Plesa-Skwerer et al 2009), although one recent study indicated a comparable level of autonomic reactivity among children with WS and typically developing (TD) children of a similar age (Järvinen et al 2015).…”
Section: Emotion Processing In Persons With Williams Syndromementioning
confidence: 99%
“…), although this may not be the case when methodological problems are overcome (Martínez‐Castilla et al . ). Nevertheless, autonomic arousal levels in response to negative emotions, such as sad or angry, have been found to be lower in individuals with WS than in comparison groups matched for age or for IQ, suggesting decreased vigilance (Plesa‐Skwerer et al .…”
Section: Introductionmentioning
confidence: 97%